Exploring the Nexus between the Organizational Entrepreneurship, Supply Chain Integration and The Performance Outcomes of Thai Textile Industry - Sumalee Srisuponvanit; Sudawan Somjai; Khomsan Laosillapacharoen; Teepakorn Boonaram (International Journal of Supply Chain Management, 2019)
With the increase of importance for collaboration, intelligence, operational integration with partners in supply chain and inter-organizational partnership, there has been change in the role of supply managers in improving corporate performance. This is reflected in the research related to firms and entrepreneurial settings. The mechanism identified in previous research studies along with the entrepreneurial skills and role of supply management have been explored in this research study. The integration of firm with its suppliers is contributed by entrepreneurial behavior as reflected by the results, which are in line with theoretical framework. This improves the performance of firm. Managers, who aim at improving performance, can achieve high performance through changes in culture and recruitment of management supply function to an entrepreneurial orientation. The implementation of organizational entrepreneurship concept to supply management theory is important. It has been suggested by this research that there is need for further investigation to give a flexible approach for using entrepreneurial constructs to define principles of supply management in the collaboration of buyer and supplier, organizational outcomes and relational capital. The implementation of organizational entrepreneurship concept to supply management theory is important. It has been suggested by this research that there is need for further investigation to give a flexible approach for using entrepreneurial constructs to define principles of supply management in the collaboration of buyer and supplier, organizational outcomes and relational capital.